Governance and Auditing the Implementation of the Sustainable Development Goals (SDGs): Challenges of the Preparedness Phase - Ali Alagla, Saleh (Finance and Business Economies Review, 2019)
This paper aims to perform an in-depth analysis of the Sustainable Development Goals (SDGs) which have been implemented by the United Nations in the year 2015. The research is based on performing an audit of the design and structured framework in order to understand the level of its successful implementation along with highlighting the grey areas and potential threats which require a proactive and strategic move. All the presentations and discussions which happened in the 15th General Auditing Bureau (GAB) Annual Seminar, being held in Saudi Arabia in the year 2018, have been assessed and evaluated to draw a conclusion. However, analysis of the discussion on the seminar has highlighted specific gaps which might challenge the efficacy of the program and hence requires a necessary action.